The Effect of Islamic Group Guidance on Student Self Efficacy - Rangkuty, Lanna Sary; Rahmi, Alfi; Yusri, Fadhilla; Syam, Hidayani (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
This research is motivated by the phenomenon that there are still many students at MTsN 6 Agam who are indicated to have low Self-Efficacy in dealing with learning situations. The aim to be achieved in this research is to find out whether there is an influence of Islamic group guidance on student Self-Efficacy at MTsN 6 Agam. The formulation of the problem in this research is whether the Islamic Group Guidance technique has a significant influence on the Self-Efficacy of class VII-8 students at MTsN 6 Agam. This type of research is pre-experimental research with a One Group Pretest Posttest Design model. The population is class VII students at MTsN 6 Agam, while the research sample is 10 students who have indicated Self-Efficacy problems based on a non-random sampling technique in the form of purposive sampling and the results of the pretest. Data collection in this research used a questionnaire. The data analysis technique uses the Wilcoxon test which requires the hypothesis to be accepted if the sig value is less than 0.05 and is assisted by the SPSS version 26 application. Based on the results of data analysis using the Wilcoxon test, the sig value is known. p-value is 0.005 ɑ (ɑ = 0.05) which means Ha is accepted and Ho is rejected. The results of the Wilcoxon test calculations can be concluded that Islamic group guidance can be an alternative for increasing student Self-Efficacy in class VII-8 MTsN 6 Agam.